The optimal structure of commodity taxation in a monopoly with tax avoidance or evasion - Laszlo Goerke (University of Tübingen, Faculty of Economics and Social Sciences, 2011)
If tax obligations are met, the balanced-budget substitution of an ad valorem tax on output for a specific tax not only raises a monopolist's production, but also represents a Pareto improvement. However, if tax avoidance or evasion is feasible and the marginal costs of such actions decline with the legal tax burden, a monopolist will respond to a balanced-budget substitution of an ad valorem tax for a specific tax by reducing output, while profits remain constant. Therefore, in the presence of tax avoidance or evasion activities a move towards specific taxation can represent a Pareto improvement.
urn:nbn:de:bsz:21-opus-56027
Keywords: H21; H25; H26; 330; Ad valorem tax; Monopoly; Output; Tax avoidance; Tax evasion; Specific tax